The Relationship Between Stress, Workload, and Motivation With The Quality of Nursing In The In patient Ward of Banten Regional Hospital - Cucu Sugianti; Harif Fadhilah; Eni Widiastuti; Muhamad Hadi; Rahayu Nawangwulan (PT. Anagata Sembagi Education, 2025)
Nursing performance is a series of activities in providing nursing care which is a process or nursing practice activity provided by nurses. in patients using the nursing process. Poor performance can be caused by ineffective leadership. As a form of supervision, a leader can using a performance appraisal system to support optimal organization. Organizing is the process of managing and directing all assets, including the workforce, to collaborate and synergize effectively and ensure that each element clearly understands their respective roles, obligations, and areas of responsibility. The purpose of this study was to identify the relationship between the leadership of the ward head and organization with the performance of nurses in the inpatient ward of the Jakarta Islamic Hospital Sukapura. The study design was cross-sectional. The number of samples in this study was 75 respondents with a selection technique using a total sampling technique. The analysis used was univariate, bivariate, and multivariate analysis. The results of the study showed a relationship between the leadership of the ward head and nurse performance (p = 0.001), there was a relationship between organizing and nurse performance (p = 0.000), there was no relationship between length of service (p = 1.000), there was no relationship between education (p = 0.783), there was no relationship between gender (p = 0.757), and there was no relationship between age and nurse performance (p = 0.658). Organization is the most dominant factor that influences nurse performance. Hospital management should evaluate the inpatient organizational structure with a more effective command flow and span of control of the ward head that allows each nurse to receive supervision, thereby improving the performance of nurses in providing nursing care services.